ANALISIS PERBEDAAN LIKUIDITAS SAHAM, HARGA SAHAM, DAN RETURN SAHAM SEBELUM DAN SESUDAH STOCK SPLIT (Studi pada Perusahaan Go Public yang Melakukan Stock Split Periode 2011-2014) - Aloysius Adimas Kristianiarso (Operations Excellence: Journal of Applied Industrial Engineering, 2014)
Abstract. This study aims to determine the difference between the stock price,stock returns and trading volume before and after the announcement of a stocksplit. The research data is the daily data for a period of four years (2011-2014).The used sampling method was purposive sampling. Out of a population of 39companies which conduct a stock split, 38 companies that meet the criteria to besampled. The analytical method used in this research is a Independent t - test. Theresults showed there was no significant difference between the stock price beforeand after the stock split, there was a significant difference between return beforeand after stock split, and there was no significant difference between tradingvolume activity before and after the stock split.Keywords: stock prices, returns, stock trading volume activity, stock split